Fixed Point Results for Weak φ-Contractions in Cone Metric Spaces over Banach Algebras and Applications - Biwen Li; Huaping Huang (Journal of Function Spaces)
By using a nontrivial proof method, the purpose of this paper is to obtain some fixed point results for weak φ-contractions in cone metric spaces over Banach algebras. Several examples and applications to the existence and uniqueness of a solution to two classes of equations are also given.